E-096 EMS provider preference comparison between the pre-hospital LVO detection during initial care transport (PREDICT) scale and the rapid arterial occlusion evaluation (RACE) scale: a subanalysis of the PREDICT study. (4th August 2020) - Fortuny, E; Cruz, A; Ugiliweneza, B; Wang, D; White, A; Khattar, N; Gallinore, B; Ding, D; Wolfe, S; Heck, D; James, R
Abstract : Intro: Accurate identification of large vessel occlusion (LVO) strokes in the field may save lives through reduced transport times. Emergency Medical Services (EMS) training is critical to the successful implementation of prehospital screening scales. The prospectively validated 6-item Rapid Arterial oCclusion Evaluation (RACE) scale is a common EMS LVO stroke scale. As part of our prospective, pre-hospital EMS Validation comparison study of the PRe-hospital ELVO Detection during Initial Care Transport (PREDICT) scale, we hypothesized that EMS providers without prior exposure to RACE would prefer the shorter, simpler PREDICT-4 scale and due to the cognitive bias known as the 'mere exposure effect, ' EMS providers with previous experience with RACE will prefer it over the new PREDICT scale. Methods: A total of 86 EMS providers were asked their preferred scale after performing both scales on a subject suspected of having a stroke. EMS providers were trained on a secure, online application to perform the PREDICT-4 scale and record both scales and complete a one-question survey (figure 1 ). A chi-square test and one-sample test of proportion was conducted to determine the preferred scale. Results: 86 EMS providers enrolled a total of 250 subjects. 38 providers enrolled only one subject and 48 enrolled 2 or more. When comparing scale preference of all studied EMS providers (both with and without previous exposure to the RACE scale prior to this study), 37.2% preferred the PREDICT 4-item scale and 62.8% preferred the RACE scale, p=0.018, 95% CI [27.7, 47.8 and 52.2, 72.2, respectively]. The planned subgroup analysis of EMS providers who did not have prior mere-exposure to the RACE scale (n=49), we found that 34.7% preferred the PREDICT 4-item scale [95% CI 22.9, 48.6%] and 65.3% preferred the RACE scale p=0.03, 95% CI [51.3, 77.0]. In the subgroup analysis of the 48 providers who enrolled ≥2, on their first screening 20 (41.6%, p=0.248, 95% CI [28.8, 55.7]) preferred PREDICT-4 and 28 (58.3%) RACE. On their last screening, only 18 (37.5%, p=0.08, 95% CI [25.2, 51.6]) providers preferred PREDICT-4. Conclusion: The shorter and simpler PREDICT scale was found to be less preferable with EMS provider all-comers, which may be partially due to the mere-exposure cognitive bias effect though this difference persisted in providers who had no prior exposure to either scale. In providers who enrolled multiple patients, there was a statistically insignificant trend towards preference for RACE between their first and last screening. Disclosures: E. Fortuny: None. A. Cruz: None. B. Ugiliweneza: None. D. Wang: None. A. White: None. N. Khattar: None. B. Gallinore: None. D. Ding: None. S. Wolfe: None. D. Heck: None. R. James: 1; C; Medtronic.